PERBANDINGAN KADAR DAN UJI MUTU FISIK INJEKSI DEXAMETHASONE SODIUM PHOSPHATE SEBELUM DAN SESUDAH MASA KADALUARSA SECARA SPEKTROFOTOMETRI UV-VIS - Ruddat Ilaina Rahmah; Nur Anggreini Dwi Sasangka; Dian Marlina (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Corticosteroids are drugs that contain synthetic steroid hormones. Dexamethasone sodium phosphate injection is a sterile preparation where a sterile preparation when opened will be exposed to air and microorganism in the surrounding environment, so that drug levels and potency will decrease. The use of steroid injection includes the use that is often used in hospitals and makes stock increase, this increase in preparations which often makes expired preparations will increase and become a problem in every hospital. This study aimed to determine the effect of storage at room temperature and refrigerator temperature on the level and physical quality of dexamethasone sodium phosphate injection before and after expiration. This study used dexamethasone sodium phosphate injection before and after expiration. The raw material for dexamethasone sodium phosphate is listed on the COA, 2022. The injection was stored at room temperature (<300C) and refrigerator temperature (2-80C) within 14 days, then organoleptic observation, pH test, and assay were carried out using UV-VIS Spectrophotometry. Quantitative analysis was carried out by comparing the levels of dexamethasone injection before and after the expiration date based on the linear regression chart and the paired sample t-test. The results obtained show that storage at room temperature and refrigerator temperature does not affect organoleptic observations, pH at the levels of dexamethasone sodium phosphate injection before and after expiration. Testing of dexamethasone sodium phosphate injection levels before and after expiration at room temperature storage (<300C) did not have a significant difference, while dexamethasone sodium phosphate injection levels before and after expiration at refrigerator temperature storage (2-80C) had a significant difference.